[18F]-Fluorodeoxyglucose PET/CT imaging as a marker of carotid plaque inflammation: Comparison to immunohistology and relationship to acuity of events. (15th November 2018) - Cocker, Myra S.; Spence, J. David; Hammond, Robert; deKemp, Robert A.; Lum, Cheemun; Wells, George; Bernick, Jordan; Hill, Andrew; Nagpal, Sudhir; Stotts, Grant; Alturkustani, Murad; Adeeko, Adebayo; et al.
Abstract: Background: [18F]-fluorodeoxyglucose ( 18 FDG) uptake imaged with positron emission tomography (PET) and computed tomography (CT) may serve as a biomarker of plaque inflammation. This study evaluated the relationship between carotid plaque 18 FDG uptake and a) intraplaque expression of macrophage and macrophage-like cellular CD68 immunohistology; b) intraplaque inflammatory burden using leukocyte-sensitive CD45 immunohistology; c) symptomatic patient presentation; d) time from last cerebrovascular event. Methods: 54 patients scheduled for carotid endarterectomy underwent 18 FDGPET/CT imaging. Maximum 18FDG uptake (SUV max ) and tissue-to-blood ratio (TBR max ) was measured for carotid plaques. Quantitative immunohistological analysis of macrophage-like cell expression (CD68) and leukocyte content (CD45) was performed . Results: 18 FDG uptake was related to CD68 macrophage expression (TBRmax : r = 0.51, p < 0.001), and total-plaque leukocyte CD45 expression (TBRmax : r = 0.632, p = 0.009, p < 0.001). 18 FDG TBRmax uptake in carotid plaque associated with patient symptoms was greater than asymptomatic plaque (3.58 ± 1.01 vs. 3.13 ± 1.10, p = 0.008). 18 FDG uptake differed between an acuity threshold of <90 days and >90 days (SUVmax :3.15 ± 0.87 vs. 2.52 ± 0.45, p = 0.015). Conclusions: In this CAIN cohort, 18 FDG uptake imaged with PET/CT serves a surrogate marker of intraplaque inflammatory macrophage, macrophage-like cell and leukocyte burden. 18FDG uptake is greater in plaque associated with patient symptoms and those with recent cerebrovascular events. Future studies are needed to relate 18 FDG uptake and disease progression. Highlights: [18F]-fluorodeoxyglucose (18FDG) uptake on positron emission tomography is validated as a marker of plaque macrophage burden. 18FDG uptake in carotid plaque is related to intraplaque leukocyte burden. Plaque in patients with symptomatic cerebrovascular disease has greater 18FDG uptake than clinically silent plaque. 18FDG uptake is related to the acuity of a cerebrovascular event.